2022
DOI: 10.1101/2022.12.11.519962
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Confusion will be my epitaph: Genome-scale discordance stifles phylogenetic resolution of Holothuroidea

Abstract: Sea cucumbers (Holothuroidea) are a diverse clade of echinoderms found from intertidal waters to the bottom of the deepest trenches. Their reduced skeletons and limited number of phylogenetically-informative traits have long obfuscated morphological classifications. Sanger-sequenced molecular datasets have also failed to constrain the position of major lineages. Noteworthy, topological uncertainty has hindered a resolution for Neoholothuriida, a highly diverse clade of Permo-Triassic age. We perform the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 97 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…This is in fact the expected behavior if topological incongruence is driven by biological factors such as ILS (Mendes & Hahn 2016). While some have argued that deep recalcitrant nodes are linked to ancient events of ILS (e.g., Cai et al 2021;Hime et al 2021;Mongiardino Koch et al 2023;Song et al 2023), it has also been suggested that topological incongruence at deep timescales is more likely to be . CC-BY-NC-ND 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This is in fact the expected behavior if topological incongruence is driven by biological factors such as ILS (Mendes & Hahn 2016). While some have argued that deep recalcitrant nodes are linked to ancient events of ILS (e.g., Cai et al 2021;Hime et al 2021;Mongiardino Koch et al 2023;Song et al 2023), it has also been suggested that topological incongruence at deep timescales is more likely to be . CC-BY-NC-ND 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 72%
“…This is in fact the expected behavior if topological incongruence is driven by biological factors such as ILS (Mendes & Hahn 2016). While some have argued that deep recalcitrant nodes are linked to ancient events of ILS (e.g., Cai et al 2021;Hime et al 2021;Mongiardino Koch et al 2023;Song et al 2023), it has also been suggested that topological incongruence at deep timescales is more likely to be caused by methodological issues related to loss of signal and model inadequacy (Gatesy & Springer 2014;Richards et al 2018). While our analyses were not designed to test this phenomenon, our results are contrary to those expected if ILS was the main driver of topological conflict at ancient nodes.…”
Section: Discussionmentioning
confidence: 75%
“…Raw files for all novel datasets, as well as those so far available only on EchinoDB [22], are deposited in the NCBI sequence read archive (SRA) under BioProject PRJNA979278. All assemblies are available at the associated Dryad data repository (doi:10.5061/dryad.0p2ngf255) [26], along with the phylogenetic matrices, trees and other results derived from them.…”
Section: Materials and Methods (A) Taxon Sampling Extraction And Sequ...mentioning
confidence: 99%
“…COI sequences are available from GenBank under accession numbers OR082743-OR082756 and OR145350-OR145353; transcriptomic raw reads are available from SRA under BioProject PRJNA979278. All assemblies, phylogenomic datasets and trees, and other results, can be obtained from the Dryad Digital Repository: https://doi.org/10.5061/dryad.0p2ngf255 [26].…”
mentioning
confidence: 99%
“…The order Apodida is a basal group in the class Holothuroidea, as shown in both morphological and molecular analyses (Kerr & Kim, 1999Lacey et al, 2005;Miller et al, 2017;Mongiardino Koch et al, 2023;Sun et al, 2021). Within the families Chiridotidae and Synaptidae, there is a diversity of developmental types: planktotrophic auricularia, lecithotrophic doliolaria, and coelomic and intraovarian brooding (Clark, 1908;Sewell et al, 2024;Smiley et al, 1991).…”
mentioning
confidence: 99%